Intermediate Technology for Food Security and Sustainable Development in the Central Rain Lands of Sudan: The Need and Justification - Bello, Abdel Raouf Suleiman (Advances in Social Sciences Research Journal, 2017)
Animal traction technology has been introduced by various rural development projects in different areas of the Sudan, as an alternative to the purely traditional, and modern agricultural technologies. The idea is aimed at introducing simple, efficient, and appropriate agricultural techniques to increase agricultural productivity and the cultivated area, as well as to promote off-farm activities in the rural areas. It is clearly noticed that the rural development projects based on animal traction in Western Sudan has achieved considerable socio-economic and environmental impacts there. These consequences range from upgrading of traditional agricultural hand tools, increasing the cultivated area to productivity per feddan, improving of local skills, and provision of jobs for some marginal groups such as black smiths, landless groups, and others.